2017
DOI: 10.1038/onc.2016.522
|View full text |Cite
|
Sign up to set email alerts
|

Detecting intratumoral heterogeneity of EGFR activity by liposome-based in vivo transfection of a fluorescent biosensor

Abstract: Despite decades of research in the epidermal growth factor receptor (EGFR) signalling field, and many targeted anti-cancer drugs that have been tested clinically, the success rate for these agents in the clinic is low, particularly in terms of the improvement of overall survival. Intratumoral heterogeneity is proposed as a major mechanism underlying treatment failure of these molecule-targeted agents. Here we highlight the application of fluorescence lifetime microscopy (FLIM)-based biosensing to demonstrate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…This association was also found to persist in the presence of an EGFR inhibitor. The same effect of macrophage infiltration on EGFR activation was also seen in colorectal cancer xenografts, but not in non-small-cell lung cancer xenografts expressing a constitutively activated EGFR mutant that could not be affected by macrophages (26).…”
Section: Imaging Kinase Activities In Tumor Tissuesmentioning
confidence: 70%
See 2 more Smart Citations
“…This association was also found to persist in the presence of an EGFR inhibitor. The same effect of macrophage infiltration on EGFR activation was also seen in colorectal cancer xenografts, but not in non-small-cell lung cancer xenografts expressing a constitutively activated EGFR mutant that could not be affected by macrophages (26).…”
Section: Imaging Kinase Activities In Tumor Tissuesmentioning
confidence: 70%
“…Notably, because FLIM is less sensitive to the loss of donor emission intensity caused by scattering in tissues, FLIM-FRET can be effectively applied in vivo. For example, Weitsman et al (26) generated a FLIM-FRET-compatible version of the EGFR activity biosensor phosphorylation indicator of CrkII chimeric unit (Picchu) (27) by replacing YFP and CFP with mRFP1 and EGFP, respectively, and used the resulting Picchu-FLIM sensor to investigate EGFR activity in tumor xenografts. Another benefit of FLIM-FRET is that it does not require fluorescence emission by the acceptor, which can potentially alleviate some challenges of ratiometric imaging, such as spectral bleed-through.…”
Section: Fret-based Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 We have recently used this approach to formulate lipopolyplexes that selectively transfected tumor cells with pDNA coding for a FRET biosensor and used this to monitor EGFR inhibition by tyrosine kinase inhibitors in vivo using quantitative FRET-FLIM imaging. 28 In this work, the bifunctional peptide incorporated peptide sequences targeting EGFR, conferring tumor selectivity and active targeting on these lipopolyplexes.…”
Section: Glycero-3-phosphoethanolamine-n-[carboxy (Polyethyleneglycolmentioning
confidence: 99%
“…We have also shown that liposomes formulated including these n‐EG lipids form nanoparticles that are shielded with a shallow, homogeneous n‐EG layer, and that these have much better cellular uptake than liposomes formulated with 1,2‐distearoyl‐sn‐glycero‐3‐phosphoethanolamine‐ N ‐[carboxy (polyethyleneglycol) 2000 ] (DSPE‐PEG2000) . We have recently used this approach to formulate lipopolyplexes that selectively transfected tumor cells with pDNA coding for a FRET biosensor and used this to monitor EGFR inhibition by tyrosine kinase inhibitors in vivo using quantitative FRET‐FLIM imaging . In this work, the bifunctional peptide incorporated peptide sequences targeting EGFR, conferring tumor selectivity and active targeting on these lipopolyplexes.…”
Section: Introductionmentioning
confidence: 99%